2003
DOI: 10.1063/1.1534917
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric loss in a C60 film observed by coupling with the external electromagnetic field of a surface acoustic wave

Abstract: The dielectric loss in C60 films was studied by a noncontacting technique utilizing the external electric fields associated with surface acoustic waves (SAW) on a piezoelectric crystal. A sharp increase in loss was observed at temperatures below 220 K together with other structure not found with standard SAW measurements. We believe that these features are due to induced current in C60, causing joule loss, and to the formation of localized dipole moments by charge transfer between adsorbed O2 and C60 molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Details of the traveling-wave method have been reported in our previous works. 25,26) The SiC sample and SAW device were set in a cryostat chamber with a residual gas pressure of less than 2:0 Â 10 À5 Pa. The temperature of the sample was controlled using a temperature controller (Conductus LTC-20C) and a cryostat (Iwatani Industrial Gases D105) in the range of 20-300 K in steps of 1 K at a rate of 0.14 K min À1 .…”
Section: Methodsmentioning
confidence: 99%
“…Details of the traveling-wave method have been reported in our previous works. 25,26) The SiC sample and SAW device were set in a cryostat chamber with a residual gas pressure of less than 2:0 Â 10 À5 Pa. The temperature of the sample was controlled using a temperature controller (Conductus LTC-20C) and a cryostat (Iwatani Industrial Gases D105) in the range of 20-300 K in steps of 1 K at a rate of 0.14 K min À1 .…”
Section: Methodsmentioning
confidence: 99%
“…We have also studied the temperature dependences of C 60 and carbon nanotube films by using this method in our previous works. 18,19 Based on the above results, we found in this study that the traveling-wave energy loss in a semiconductor is proportional to Joule heat caused by current of the charge wave. Therefore, we can determine concentration and mobility of the carriers in semiconductor by measuring the travelingwave loss.…”
Section: Introductionmentioning
confidence: 93%
“…, at 270 K for 10 18 cm À3 and below 100 K for 10 16 cm À3 of the concentration. 21 In the high-frequency measurement of this study, the traveling-wave changes effectively the balance between lattice and ion scatterings as well as their temperature dependences.…”
Section: à3mentioning
confidence: 99%
“…[40][41][42] It has been used to characterize the drift mobility of semiconductors, 43 electromagnetic properties of two-dimensional electron system (2DES) on GaAs/Al x Ga 1-x As heterojunctions, 44,45 acoustoelectric currents in magnetic thin films, 46 superconducting properties of thin films, 47 and charge carrier mobility in organic thin films. 48 We have also reported several results obtained using this measurement method, for example, dielectric properties of C 60 and carbon nanotube films, 49,50 excitation states of antimony impurity in silicon, 51 ionization energies of nitrogen impurity in 4H-SiC crystal 52 in our previous works. By increasing coupling area of the sample with external electric field, we found that this method is very effective for characterizing ultra-thin sample.…”
Section: Introductionmentioning
confidence: 99%